2019
DOI: 10.3389/fonc.2019.00532
|View full text |Cite
|
Sign up to set email alerts
|

The WNT Pathway Is Relevant for the BCR-ABL1-Independent Resistance in Chronic Myeloid Leukemia

Abstract: Notwithstanding the introduction of Tyrosine Kinase Inhibitors (TKIs) revolutionized the outcome of Chronic Myeloid Leukemia (CML), one third of patients still suspends treatment for failure response. Recent research demonstrated that several BCR/ABL1-independent mechanisms can sustain resistance, but the relationship between these mechanisms and the outcome has not yet been fully understood. This study was designed to evaluate in a “real-life” setting if a change of expression of several genes involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Moreover, about the low rate of TTV replication during treatment with nilotinib, we can hypothesize that some "antiviral" genes could be more expressed. In our previous study, we observed that imatinib upregulated two "antiviral" genes: Interferon-stimulated gene 15 (ISG15) and Mov10 RISC Complex RNA Helicase (MOV10) (67). ISG15 has been reported to exert a direct negative effect on viral replication, probably by restoring autophagy and sustaining NK proliferation and dendritic cell maturation (68).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, about the low rate of TTV replication during treatment with nilotinib, we can hypothesize that some "antiviral" genes could be more expressed. In our previous study, we observed that imatinib upregulated two "antiviral" genes: Interferon-stimulated gene 15 (ISG15) and Mov10 RISC Complex RNA Helicase (MOV10) (67). ISG15 has been reported to exert a direct negative effect on viral replication, probably by restoring autophagy and sustaining NK proliferation and dendritic cell maturation (68).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AGO1 regulates the transcription activity by stimulation of PI3K signaling [14]. Wnt pathway through PI3K signaling is involved in CML progression and therapeutic resistance [15]. This can give the basis of considering rs636832 as a bad prognostic as well poor therapeutic marker of CML in the present study.…”
Section: Genotypes and Clinical Criteria Of CML Patientsmentioning
confidence: 90%
“…As well AGO1 was found to regulate the transcription activity through stimulation of phosphoinositide 3-kinase (PI3K/AKT) [14]. Wnt pathway activation with subsequent PI3K/AKT signaling; is involved in CML progression and TKIs resistance [15]. Hence, AGO1 variants may participate in CML risk and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Porcupine (PORCN)-dependent acetylation of Wnt ligands is essential in Wnt/β-catenin signalling for maintenance of cellular functions [ 17 , 178 , 179 ]. BCR-ABL1 drives constitutive secretion of Wnt-ligands and overexpression of frizzled-4 (FZD4) receptors to promote nuclear transduction and stabilization of β-catenin, mediating TKI-resistance [ 178 , 179 , 180 ]. Riether et al proposed that it might be induced by prolonged TKI exposure as TKI-therapy depleted miR29 and amplified CD70 expression, leading to CD27-mediated Wnt activation for LSC quiescence and therapy resistance [ 181 ].…”
Section: Targeting the CML Stem Cell Microenviroment Survival Andmentioning
confidence: 99%